Takhrij and Syarah Hadith of Agrotechnology Oil Processing Plants in Modern Era - Zaky Nur Fadilah; Wahyudin Darmalaksana; Asep Seful Mimbar; Ahmad Taofik (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith regarding the processing of oil from plants in the modern era. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research is that oil produced from agricultural products in the form of olives has various benefits for humans and its use is recommended by the Prophet. The conclusion of this research is takhrij and syarah hadith regarding the processing and benefits of plant oil, especially from olives, which are very useful in the modern era.